Mapping Hungarian secondary school students’ digital and AI literacy with a focus on language learning - Ujlaki, János (GILE Journal of Skills Development, 2025)
As digital technologies and artificial intelligence (AI) increasingly shape education, students must acquire the competencies necessary to navigate these tools critically and ethically. Although digital literacy has been extensively explored in higher education contexts, research on secondary school students remains limited. This study addresses this gap by mapping Hungarian secondary school students’ digital and AI literacy using the Digital Intelligence Framework (DQ Institute, 2019) and the Quebec Digital Competency Framework (Conseil supérieur de l’éducation, 2019). An online questionnaire (N = 130) assessed six competency dimensions, including ethical AI use, critical evaluation, and communication. Quantitative data analysis was conducted using SPSS, through descriptive statistics, ANOVA, correlation, and regression. Findings reveal significant differences in AI ethics and responsibility by school type and in communication-related skills based on self-assessed English proficiency, with lifelong learning predicting AI confidence. The findings highlight the need for context-sensitive, ethical, and skill-integrated AI literacy education at the secondary level. By aligning with internationally recognized frameworks, the study informs policy and practice, promoting equitable, future-ready skill development.